Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3164/jcbn.22-40
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of copper and zinc in the pathogenesis of vascular dementia

Abstract: Copper and zinc are essential for normal brain functions. Both are localized in presynaptic vesicles and are secreted into synaptic clefts during neuronal excitation. Despite their significance, excesses of copper and zinc are neurotoxic. In particular, excess zinc after transient global ischemia plays a central role in the ischemia-induced neurodegeneration and pathogenesis of vascular type senile dementia. We previously found that sub-lethal concentrations of copper remarkably exacerbated zinc-induced neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 96 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…However, under pathological conditions such as transient global ischemia, sustained excitation of neurons occurs for prolonged periods in broad areas of the brain, and excess Zn and Cu are simultaneously secreted into the same synaptic clefts for a long period of time. We have demonstrated that a sublethal concentration of Cu (5 µM) significantly exaggerated 30 µM Zn-induced neurotoxicity (molar ratio of Zn:Cu = 6:1) [123]. Therefore, it is possible that the coexistence of Cu triggers the production of ROS and cooperatively enhances Zn-induced neurotoxicity, finally causing vascular-type dementia.…”
Section: Hypothesis: Cross-talk Occurs Between Trace Elements and Amy...mentioning
confidence: 91%
See 1 more Smart Citation
“…However, under pathological conditions such as transient global ischemia, sustained excitation of neurons occurs for prolonged periods in broad areas of the brain, and excess Zn and Cu are simultaneously secreted into the same synaptic clefts for a long period of time. We have demonstrated that a sublethal concentration of Cu (5 µM) significantly exaggerated 30 µM Zn-induced neurotoxicity (molar ratio of Zn:Cu = 6:1) [123]. Therefore, it is possible that the coexistence of Cu triggers the production of ROS and cooperatively enhances Zn-induced neurotoxicity, finally causing vascular-type dementia.…”
Section: Hypothesis: Cross-talk Occurs Between Trace Elements and Amy...mentioning
confidence: 91%
“…Several antioxidants were found to attenuate Cu-enhanced Zn-induced neurotoxicity. Therefore, Cu may collaborate with Zn and play key roles in Zn-induced neurotoxicity by producing ROS, finally leading to the pathogenesis of VD [123].…”
Section: Vascular-type Senile Dementiamentioning
confidence: 99%
“…This leads to oxidative stress and endoplasmic reticulum stress that may finally lead to neurodegeneration. 44 There is more evidence of zinc and copper related toxicities leading to AD. However, this also may be involved in PD.…”
Section: Insulin-like Growth Factor-1 (Igf-1)mentioning
confidence: 99%
“…Moreover, zinc supplementation in high doses compromises copper uptake and vice versa. Adequate zinc and copper homeostasis is known to be important for decades and an altered copper/zinc ratio is found in multiple diseases, such as neurodegenerative disorders [ 125 , 126 ], hepatocellular and gastric carcinoma [ 127 , 128 ], immunological disorders such as sickle cell disease [ 129 ], and bacterial and viral infectious diseases such as leishmaniosis or COVID-19 [ 130 , 131 ]. In future, it may possible that the copper/zinc ratio may be considered as a biomarker for disease or for mortality in the elderly population.…”
Section: Zinc and Nutritional Immunitymentioning
confidence: 99%